(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article analyzes the application of lime waste (sludge) to foam concrete and the results of a study of the thermal insulation of lime waste foam concrete and the compressive strength of structural foam concrete, various ratios of solid lime waste to lime waste for more efficient use in the development of new foam concrete building materials and based on laboratory experiments it was found that lime waste (sludge) foam concrete can be used as a filler.